Pharmaceutical Prospects of Curcuminoids for the Remedy of COVID-19: Truth or Myth - Fu, Yaw-Syan; Ho, Wan-Yi; Kang, Ning; Tsai, May-Jywan; Wu, Jingyi; Huang, Liyue; Weng, Ching-Feng (Frontiers in Pharmacology, 2022)
Coronavirus disease 2019 (COVID-19) is caused by a Severe Acute Respiratory Syndrome-Coronavirus 2 (SARS-CoV-2), which is a positive-strand RNA virus and has rapidly spread worldwide as a pandemic. The vaccines, repurposed drugs, and specific treatments have led to a surge of novel therapies and guidelines nowadays, however, the epidemic of COVID-19 is not fully combated and is still in a vital crisis. In repositioning drugs, natural products are gaining attention because of the large therapeutic window and potent antiviral, immunomodulatory, anti-inflammatory, and antioxidant properties. Of note, the predominant curcumoid extracted from turmeric (Curcuma longa L.) including phenolic curcumin influences multiple signaling pathways and has demonstrated to possess anti-inflammatory, anti-oxidant, antimicrobial, hypoglycemic, wound healing, chemopreventive, chemosensitising, and radiosensitising spectrums. In the present review, all current information related to curcumin-used for anticipated treatment and prevention of severe acute respiratory syndrome-coronavirus 2 (SARS-CoV-2) infection in the studies of in vitro, in vivo, in silico, in clinical trial, and new formulation design are retracted to re-evaluate the applicant based on the pharmaceutical efficacy of clinical therapy. And it provides deep insight into appraisal esteemed knowledge and strategy about curcumin's role as an immune-booster, inflammatory modulator and therapeutic agent against COVID-19. Moreover, this article will also afford a favorable application or approach with evidence-based on the drug discovery and development, pharmacology, functional foods, and nutraceuticals for effectively fighting COVID-19 pandemic